193k views
2 votes
From the sum of a2−2ab+b2 and 2a2+2ab+b2 subtract the sum of a2−b2 and a2+ab+3b2

Every 2 in this problem is meant to be a power of 2

User Sidverma
by
5.2k points

2 Answers

5 votes

Answer: So the other guy's work is correct but he messed up on the answer. The answer is
-a^2+ab\\.

User Sarker
by
5.3k points
0 votes

Answer:


a^2-ab

Explanation:

We need to find the sum of
a^2-2ab+b^2 and
2a^2+2ab+b^2 first.

Adding
a^2-2ab+b^2 +
2a^2+2ab+b^2

Combining like terms, we get


a^2+2a^2=3a^2

-2ab+2ab = 0


b^2+b^2=2b^2

Therefore,


a^2-2ab+b^2 +2a^2+2ab+b^2=3a^2+2b^2.

Now, we need to find the sum of
a^2-b^2 \ \ and \ \ a^2+ab+3b^2..

Adding
a^2−b^2+a^2+ab+3b^2.

Combining like terms, we get


a^2+a^2=2a^2


-b^2+3b^2=2b^2.

Therefore,


a^2−b^2+a^2+ab+3b^2=2a^2+ab+2b^2.

Now, subtracting


3a^2+2b^2 -(2a^2+ab+2b^2).

Distributing minus sign over second parenthesis, we get


3a^2+2b^2-2a^2-ab-2b^2.

Combining like terms,


3a^2-2a^2=a^2


2b^2-2b^2=0

Therefore,


3a^2+2b^2-2a^2-ab-2b^2=a^2-ab.

Therefore, the difference of the sum of
a^2-2ab+b^2 +
2a^2+2ab+b^2 and
a^2-b^2+a^2+ab+3b^2. is
a^2-ab.

User Maxcanna
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.